'We Didn't Need to Know About Everything All at Once': Using UX to Give Students Easy Access to Relevant Assessment Resources - Bassett, Mark; Wattam, Craig (Australasian Society for Computers in Learning in Tertiary Education, 2024)
Tertiary student engagement with information and academic literacy online resources provided by centralized units is low. Although these resources are designed to prepare students for their assessments, they are often positioned peripherally to students’ learning environments. In attempting to position resources within students’ learning environments, our Library team conduct regular user experience (UX) testing of a course we have designed in our institution’s learning management system. Our two-year UX project has focused on the design and organization of resources that show students examples and guidance with how to do their assessments. Over two rounds of data collection and analysis, UX methods of usability testing, card sorting, low-fidelity wireframing, and high-fidelity prototyping helped identify student preferences for organising and accessing our resources. Findings indicate that students value the provision of relevant examples and guidance that show them what is expected in assessments and that they want direct access to that content as part of their courses. Implications for design include maximizing ease of use by positioning links to relevant examples and guidance in the assessment instructions and/or specific learning materials of courses, with the content being linked to positioned within a centralized repository in the same online learning environment.
Keywords: 46 Information and Computing Sciences; 39 Education; 3904 Specialist Studies In Education; Clinical Research